Static analysis of tympanic membrane in aero-otitis media by three-dimensional model of the middle ear. Issue 2 (February 2022) - Sun, Kaili; Bie, Xu; Feng, Zhixing; Yu, Shen; Sun, Xiuzhen; Wang, Jizhe; Liu, Yingxi; Peng, Lina; Yao, Zhaoxu
Highlights: In this work, we established a numerical model of the middle ear and combined it with the clinical data of aero-otitis media. We use the numerical model of middle ear to simulate the impact of aircraft altitude and speed changes on the TM during the descent phase. We found that the stress and strain of TM increase as the altitude difference and speed of the aircraft increase, and the maximum stress and strain areas are consistent with the clinical observation of TM hyperemia. For chronic recurrent aero-otitis media, tympanostomy tube placement can be considered. Abstract: The three-dimensional (3D) model of the middle ear is of great significance to the research of middle ear related diseases. The particular focus of this work is to simulate the impact of aircraft altitude and speed changes on the tympanic membrane (TM) during the descent phase, so as to analyze the pathogenesis of aero-otitis media and the mechanical response characteristics of TM under static pressure. The simulations showed that the stress and strain of TM increase as the altitude difference and speed of the aircraft increase, and the maximum stress and strain areas are consistent with the clinical observation of TM hyperemia. Therefore, among many prevention and treatment measures of aero-otitis media, it is a therapeutic method to directly balance the pressure difference between the inner and outer TM.